Iron Ball Launcher Platform Control System for Impact Test at Glass Testing Laboratory - Iwan Awaludin; Muhammad Rizqi Sholahuddin; Yudi Widhiyasana; Sofy Fitriani (Jurnal Serambi Engineering, 2025)
This study presents the digital transformation of a glass impact test system at the Center for Standardization and Services for the Ceramic and Non-Metallic Mineral Industry (BBK) through Industry 4.0 integration. The legacy system faced challenges including manual distance measurement, outdated safety components, mechanical momentum causing positioning inaccuracy, and inability to sequentially launch multiple iron balls. To address these, a phased approach was implemented: analysis, design, implementation, and testing of a digital control system. Key upgrades included LIDAR-based wireless distance sensing (up to 9 meters), RS-485 communication for reliable data transfer, replacement of 1980s-era fuses with modern Mini Circuit Breakers, and algorithmic compensation for mechanical delay. A microcontroller-based control system enabled automated height adjustment, mode selection per national standards, and sequential ball release. The system was tested across six height settings with five trials each, achieving an error rate below 1% in all cases. Results confirm enhanced precision, safety, and efficiency. This targeted digitalization demonstrates how Industry 4.0 technologies can modernize legacy testing equipment without full replacement, offering a cost-effective, scalable model for industrial laboratories undergoing digital transformation.